Method for rapidly degrading BPA based on iron-nitrogen co-doped shaddock peel biochar activated PMS

By co-doping iron and nitrogen pomelo peel biochar to activate PMS, the problem of BPA removal in environmental water bodies was solved, efficient and stable degradation effect was achieved, and the broad-spectrum degradation ability of a variety of organic pollutants was demonstrated, reducing costs and energy Consumption.

CN119259095APending Publication Date: 2025-01-07NANJING FORESTRY UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411352815.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove bisphenol A (BPA) in environmental water bodies, and conventional sewage treatment plants cannot completely remove low concentrations of endocrine disturbances. Traditional methods have problems such as high energy consumption, complex equipment, and difficulty in regeneration of catalysts.

Method used

The catalyst was prepared by using iron-nitrogen co-doped pomelo peel biochar to quickly degrade BPA to achieve efficient and stable degradation effect.

Benefits of technology

Under the conditions of the catalyst dosage of 0.1 g/L, the PMS dosage of 0.1 g/L, and the BPA concentration of 10 mg/L, BPA completely degraded within 20 minutes. The catalytic reaction system has significant degradation efficiency and stability. The toxicity of intermediate products decreased, and the degradation rate of the catalyst remained 72.2% after three cycles, and it had excellent degradation effect on a variety of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259095A_ABST
    Figure CN119259095A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly degrading BPA based on activation of PMS by iron-nitrogen co-doped pomelo peel biochar, and belongs to the field of treatment of emerging organic pollutants in environmental water. The method comprises the following steps: mixing iron-nitrogen co-doped shaddock peel biochar with a BPA solution, performing ultrasonic stirring, adding a PMS stock solution, and performing stirring to degrade BPA; wherein the use amount of the iron and nitrogen co-doped shaddock peel biochar is 0.05 g / L to 0.2 g / L. According to the method, the shaddock peel is used as the biochar, and the prepared iron-nitrogen co-doped shaddock peel biochar catalyst and a PMS catalytic system have efficient, stable and complete degradation capacity on emerging organic pollutants and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of treatment of emerging organic pollutants in environmental water bodies, and specifically relates to a method for rapidly degrading BPA based on iron-nitrogen co-doped grapefruit peel biochar activated PMS. Background Art

[0002] Emerging contaminants (ECs) are different from conventional pollutants. They are organic micropollutants and exogenous chemicals that disrupt the endocrine system. They refer to substances in the environment that can interfere with various aspects of the human or animal endocrine system and cause abnormal effects. Endocrine glands mainly include the thyroid gland, adrenal gland, pituitary gland, and some kidneys, liver, gonads, and heart. Emerging contaminants are characterized by biological toxicity, environmental persistence, and bioaccumulation. Even at low concentrations in the environment, they may pose significant environmental and health risks, and their hazards are potential and hidden. At present, there is no consensus on the classification of emerging contaminants, but they can usually be divided into endocrine disruptors (EDCs), pharmaceuticals and personal care products (PPCPs), perfluorinated compounds (PFCs), and drinking water disinfection by-products (DBPs). ECs can enter the water environment through incomplete treatment of sewage treatment plants (including domestic sewage, industrial wastewater, and hospital wastewater), sewer leaks, and underground seepage, and continue to migrate and accumulate in it.

[0003] EDCs include a variety of inorganic and organic molecules of natural or synthetic origin. Natural compounds with endocrine disrupting potential include metals and metalloids, parabens, polyaromatic hydrocarbons (PAHs), and phytoestrogens. Man-made synthetic chemicals are commonly used in industry (solvents, flame retardants, preservatives, emulsifiers, fracking chemicals), agricultural practices (pesticides, insecticides and fungicides), and health care (contraceptives, fungicides, IV bags and catheters, disposable gloves, disinfectants), as well as packaging (food storage materials, plastics), and consumer products (household chemicals, cosmetics, flame retardants, building materials, children's toys, electronic products, cooking utensils). EDCs tend to be characterized by a wide variety, low concentrations, and strong toxic effects. These compounds have certain chemical activity, and the harm to organisms is mainly manifested in the harm to the reproductive system, immune system, neurosecretory system, and carcinogenic effects. Even at trace levels, EDCs have a strong effect on the endocrine system and can even bioaccumulate in the body. EDCs cause a variety of public health disorders, such as reproductive abnormalities, obesity, various cancers, cardiovascular risks, metabolic disorders, epigenetic alterations, autism, etc. Humans are exposed to a variety of environmental chemicals known to have endocrine disrupting properties, including many molecules that humans are frequently exposed to, such as arsenic, bisphenol A (BPA), and phthalates, as well as legacy compounds that are highly chemically and biologically stable and can persist in the environment despite regulatory actions to eliminate or reduce their use.

[0004] Bisphenol A (BPA) is a typical ECs with the chemical formula C 15 H 16O2. BPA is a typical synthetic endocrine disruptor, present in certain resins and also used as a plasticizer for plastic products, such as polycarbonate plastics (such as water bottles) and epoxy resins, which are used to coat the inside of metal products (food cans, bottle caps and water supply pipes). Due to the widespread use of BPA and its analogs, BPA was detected in 75% of food samples and is often detected in human urine and blood. In addition, BPA has also been detected in the placenta, umbilical cord blood of newborns, amniotic fluid and fetal tissue. Exposure to endocrine disruptors may also occur during medical procedures due to the use of chemicals in the manufacture of medical devices (such as tubes, syringes, tablets and implants). Some common medical exposures include BPA. In the neonatal intensive care unit, BPA was detected in nearly 60% of medical devices. BPA is widely known for its estrogenic activity, however, it has also been shown to have anti-androgenic activity and the ability to regulate glucocorticoids, peroxisome proliferator-activated receptors (PPAR) and the thyroid system. Therefore, it can cause endocrine disorders in various systems, including the salivary glands, thyroid glands and male genetic system. BPA induces hormone production, which increases the risk of breast cancer in humans, and as an anti-androgen, it can have an adverse effect on male feminization. At the same time, BPA is neurotoxic and has adverse effects on cell division and plant growth.

[0005] Conventional sewage treatment plants can remove various pollutants from wastewater, including suspended and colloidal particles, dissolved organic matter, nutrients and pathogens, and play a vital role in controlling the fate and transport of EDCs in the water environment. However, they are not specifically designed to effectively remove EDCs. These compounds can easily pass through the treatment system and be discharged into the environment, so water treatment plants can remove a large amount of EDCs, and the treatment process cannot eliminate low concentrations of EDCs in water. At present, the treatment of new pollutants in water bodies mainly includes the following four technologies: adsorption, biological methods, membrane separation and advanced oxidation technology. The adsorption method separates organic pollutants from water bodies through adsorbents. It has the advantages of simple operation and low energy consumption. It is suitable for resource treatment of high-concentration wastewater or deep treatment of low-concentration wastewater. However, the adsorption process is only the transfer of organic pollutants between phases, and it cannot really remove new pollutants. In addition, the adsorption system is easily interfered by coexisting inorganic salts and natural organic matter. Biological methods utilize the metabolism of microorganisms to degrade and transform pollutants, and have the advantage of low operating costs. The sludge produced in traditional sewage treatment plants may lead to the secondary release of new pollutants into the water. Therefore, the current treatment focus is on artificial wetlands, which have the characteristics of low energy consumption, good compatibility, and high ecological value. However, although artificial wetlands have good treatment effects, they occupy a large area and are easily affected by external conditions, which limits their large-scale application. The membrane separation method uses pressure or concentration difference as the driving force to achieve the interception of pollutants by the membrane. According to the membrane pore size, it can be divided into microfiltration, ultrafiltration, nanofiltration, reverse osmosis, etc. Membrane separation technology has a good ECs removal effect, but the membrane surface is easily adsorbed by suspended matter and complex organic matter in the wastewater to form dirt and cause blockage. The later maintenance cost is too high, and further optimization is needed in practical applications. Advanced oxidation processes (AOPs) degrade and mineralize pollutants by generating highly oxidizing species (hydroxyl radicals (·OH), sulfate radicals (SO4·-), superoxide radicals (O2-·), etc.). They have unique advantages in treating ECs: (1) the generated highly oxidizing species can convert ECs into non-toxic or low-toxic small molecules through substitution, addition, electron transfer, etc.; (2) they have a wide range of applications and can degrade most organic pollutants in the environment; (3) they are simple to operate and have few operating restrictions; (4) they have high removal efficiency and can be further improved by combining with other technologies. Currently, common AOPs include photocatalytic oxidation, electrocatalytic oxidation, Fenton oxidation, ozone oxidation, persulfate oxidation, etc. However, advanced oxidation technologies have the problems of high energy consumption, complex equipment, increased costs, metal ion leaching, and difficulty in catalyst regeneration.

[0006] Carbon material activation technology has the advantages of easy availability of raw materials, good biocompatibility, and large specific surface area. 2Hybrid structures, defect sites, graphitized structures, etc. can all serve as active sites to promote the activation of PMS. Carbon materials activate PMS mainly through free radical and non-free radical pathways. The inert electronic structure and scarce active sites of original carbon materials have low catalytic performance, which limits the practical application of carbon materials. Therefore, element doping is used to adjust the electronic structure of carbon materials and increase catalytic sites.

[0007] Biochar (BC) can be prepared from a variety of biomass under high temperature conditions under anoxic or anaerobic conditions. In addition to the generated CO2, volatile oils, tar substances and combustible gases, a solid phase material with rich microporous structure is generated. Many biomass resources such as sludge, rice straw, and cow dung can be used as raw materials for the preparation of biochar. The basic components of biochar are C, H, O, N, etc. It has rich pore structure, high specific surface area and rich functional groups, such as phenolic hydroxyl, carbonyl, carboxyl, etc. There are also some nitrogen-containing and sulfur-containing functional groups, and it has a highly aromatic structure. The above structural characteristics give biochar good stability and adsorption capacity. At the same time, there are abundant surface oxygen-containing groups on biochar, which can effectively catalyze the degradation of organic pollutants. The main methods for preparing biochar are pyrolysis carbonization and hydrothermal carbonization. Pyrolysis carbonization is a method of thermally decomposing biomass under oxygen-limited or oxygen-deficient conditions at a high temperature (500-1000℃). The pyrolysis process generally uses biomass with low moisture content (<30%). Hydrothermal carbonization converts biomass with high moisture content into hydrothermal char at lower temperature (180-250℃) and self-generated pressure. Pyrolytic charcoal usually has higher specific surface area (SSA) and porosity than hydrothermal charcoal, while hydrothermal charcoal has higher surface oxygen groups (OFG) than pyrolytic charcoal.

[0008] Therefore, it is necessary to provide a method for rapidly degrading BPA based on iron-nitrogen co-doped grapefruit peel biochar activated PMS. Summary of the invention

[0009] In view of the above problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for rapidly degrading BPA based on iron-nitrogen co-doped grapefruit peel biochar to activate PMS. The method activates PMS by iron-nitrogen co-doped grapefruit peel biochar, and degrades BPA efficiently, stably and completely. The second technical problem to be solved by the present invention is to provide a method for preparing an iron-nitrogen co-doped grapefruit peel biochar catalyst. The method uses a hydrothermal-pyrolysis combined reaction to prepare an iron-nitrogen co-doped grapefruit peel biochar catalyst, which is simple and convenient. The third technical problem to be solved by the present invention is to provide an application of an iron-nitrogen co-doped grapefruit peel biochar catalyst in the degradation of emerging organic pollutants, which is used to completely degrade BPA in water bodies.

[0010] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0011] A method for rapidly degrading BPA based on iron-nitrogen co-doped grapefruit peel biochar activating PMS, comprising mixing the iron-nitrogen co-doped grapefruit peel biochar with a BPA solution, ultrasonically stirring, adding a PMS reserve solution, stirring, and degrading BPA; wherein the amount of the iron-nitrogen co-doped grapefruit peel biochar is 0.05 g / L to 0.2 g / L.

[0012] Furthermore, the dosage of the iron-nitrogen co-doped grapefruit peel biochar is 0.1 g / L.

[0013] Furthermore, the dosage of the PMS is 0.05 g / L to 0.2 g / L.

[0014] Furthermore, the dosage of the PMS is 0.1 g / L.

[0015] Furthermore, the concentration of the BPA solution is 5-40 mg / L.

[0016] Furthermore, the concentration of the BPA solution is 10 mg / L.

[0017] Furthermore, the initial solution pH of the iron-nitrogen co-doped grapefruit peel biochar / PMS system is 3-9.

[0018] Furthermore, the initial solution pH of the iron-nitrogen co-doped grapefruit peel biochar / PMS system is 3-8.

[0019] The preparation method of iron-nitrogen co-doped grapefruit peel biochar has the following specific steps:

[0020] 1) crushing the grapefruit peel and sieving it through a 100-mesh sieve to obtain grapefruit peel powder;

[0021] 2) adding pomelo peel powder, urea, FeSO4·7H2O and ascorbic acid into deionized water, stirring magnetically to dissolve, then placing into an autoclave and hydrothermally heating at 190°C for 6 hours, centrifuging after the hydrothermal reaction, collecting the precipitate, and freeze-drying at -60°C for 36 hours to obtain hydrothermal pomelo peel charcoal; wherein the mass ratio of pomelo peel powder, urea, FeSO4·7H2O and ascorbic acid is 1:1:0.6-0.8:0.3-0.5;

[0022] 3) The hydrothermal grapefruit peel charcoal prepared in step 2) was placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min, and calcined for 2 hours under N2 protection. After the calcination, it was first washed with 5 mol / L hydrochloric acid for 12 hours, and then washed with deionized water for 3 times to prepare an iron-nitrogen co-doped grapefruit peel biochar catalyst.

[0023] Application of the iron-nitrogen co-doped grapefruit peel biochar prepared by the method in degrading BPA.

[0024] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0025] (1) The Fe-N@PPBC prepared by the present invention activated PMS to catalyze the degradation of BPA. Under the conditions of catalyst dosage of 0.1 g / L, PMS dosage of 0.1 g / L, BPA concentration of 10 mg / L, and pH 0 of 6.45, the Fe-N@PPBC catalytic system degraded 100% of BPA within 20 minutes.

[0026] (2) The Fe-N@PPBC / PMS catalytic reaction system of the present invention has significant degradation efficiency and stability.

[0027] (3) In the process of using Fe-N@PPBC / PMS to degrade BPA in the present invention, the toxicity of various intermediates in the degradation pathway showed a downward trend or was negative.

[0028] (4) The degradation rate of BPA by Fe-N@PPBC prepared by the present invention remains at 72.2% after three cycles, and the catalytic performance recovers after re-calcination.

[0029] (5) The Fe-N@PPBC prepared by the present invention has a broad-spectrum degradation ability for organic pollutants, and has excellent degradation effects on sulfamethazine (SMT), sulfadiazine (SDZ), rhodamine B (RhB), tetracycline (TC) and ciprofloxacin (CIP).

[0030] (6) Compared with the existing carbon catalysts, the Fe-N@PPBC of the present invention uses green and low-cost agricultural and forestry waste grapefruit peel, and the doping raw materials are also low-cost urea and iron salt. The present invention does not need to add any pore-forming agent due to the natural foam structure of grapefruit peel, and the pyrolysis temperature is relatively low (700°C), which can achieve the dispersion and full exposure of iron and nitrogen sites, and fully contact and react with pollutants, thereby achieving excellent degradation rate and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the ESEM image of the catalyst of the present invention;

[0032] Figure 2 is a pore size distribution diagram of the catalyst of the present invention;

[0033] Figure 3 is the XRD spectrum of the catalyst of the present invention;

[0034] Figure 4 The removal rate of BPA under different catalytic systems is shown in Figure 2.

[0035] Figure 5 The graph of the dosage of the Fe-N@PPBC catalyst of the present invention on the BPA removal rate (a) and the reaction rate constant (b);

[0036] Figure 6 The graphs of the PMS dosage of Fe-N@PPBC of the present invention on the BPA removal rate (a) and the reaction rate constant (b);

[0037] Figure 7 The graphs of pollutant concentration on BPA removal efficiency (a) and reaction rate constant (b);

[0038] Figure 8 The graphs of the system pH on BPA removal rate (a) and reaction rate constant (b);

[0039] Fig. 9 The effect of coexisting ions on BPA removal efficiency (a) and the reaction rate constant (b) are shown in the graph;

[0040] Fig.10 Figure 2 shows the cyclic performance of Fe-N@PPBC (a) and the iron ion leaching concentration in a single cycle (b).

[0041] Fig.11 This is the result diagram of the removal rate of BPA by the Fe-N@PPBC / PMS system in Xuanwu Lake water / tap water;

[0042] Fig.12 This is the removal rate spectrum of Fe-N@PPBC / PMS system for different types of pollutants. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with specific embodiments.

[0044] Bisphenol A used in the following examples was sourced from MacLean Reagent Co., Ltd.; urea, FeSO4·7H2O and ascorbic acid were sourced from Aladdin Reagent Co., Ltd., and grapefruit peel was commercially available.

[0045] The following examples use a high performance liquid chromatograph (Thermo Fisher U3000) to measure the BPA concentration, using a C18 column, the column oven is set to 30°C; a methanol / 0.1% phosphoric acid solution (70:30, v / v) mixture is used as the mobile phase, the flow rate is set to 1.2 mL / min; the detection wavelength is 276 nm; the injection volume is 10 μL, and the residence time is 6.1 min. The BPA removal rate is calculated as follows:

[0046]

[0047] Where, C0 is the initial concentration of BPA (mmol / L), t is the reaction time (min), C t is the concentration of BPA in the system when the reaction time is t (mmol / L), and n is the removal rate of BPA (%).

[0048] The degradation process of BPA by the system was fitted with a pseudo first-order degradation kinetic model to evaluate the degradation efficiency of BPA. The calculation method is as follows:

[0049]

[0050] The following examples PMS concentration was determined by iodine titration: 0.5 mL of the reaction solution was taken, filtered to remove the catalyst, and the filtrate was added to 4.5 mL of KI solution (0.5 mol / L, containing NaHCO3, 0.05 mol / L). Wait for 30 min to allow the reaction to proceed fully. Finally, the sample was detected by UV-Vis spectrophotometer at a wavelength of 352 nm.

[0051] Example 1

[0052] 1. The preparation method of Fe-N@PPBC is as follows:

[0053] (1) Cut the grapefruit peel into pieces and completely crush them with a crusher, and then sieve them through a 100-mesh sieve to obtain grapefruit peel powder;

[0054] (2) 3 g of grapefruit peel powder, 3 g of urea (nitrogen source), 0.695 g of FeSO4·7H2O (iron source) and 0.3125 g of ascorbic acid (reducing agent) were added to 50 mL of deionized water and dissolved by magnetic stirring. The mixed solution was then transferred to a 100 mL Teflon-lined autoclave and hydrothermally heated at 190 °C for 6 h. After the hydrothermal reaction was completed, the reaction mixture was centrifuged, the precipitate was collected, and freeze-dried at -60 °C for 36 h to obtain hydrothermal grapefruit peel charcoal.

[0055] (3) The hydrothermal grapefruit peel charcoal prepared in step (2) was placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min, and calcined for 2 h under N2 protection. After calcination, it was first washed with hydrochloric acid for 12 h and then washed with deionized water for 3 times to prepare Fe-N@PPBC.

[0056] 2. The preparation method of PPBC is as follows:

[0057] The urea and FeSO4·7H2O are removed from step (2) of the preparation method of Fe-N@PPBC, and the remaining steps are exactly the same as the preparation method of Fe-N@PPBC to prepare PPBC.

[0058] 3. The preparation method of N@PPBC is as follows:

[0059] In step (2) of the preparation method of Fe-N@PPBC, FeSO4·7H2O is removed, and the remaining steps are exactly the same as the preparation method of Fe-N@PPBC to prepare N@PPBC.

[0060] The PPBC, N@PPBC and Fe-N@PPBC prepared above were characterized.

[0061] 4. Catalyst morphology and structure

[0062] The present invention uses environmental scanning electron microscopy (ESEM) to analyze the surface morphology of the catalyst. Figure 1 shown.

[0063] Figure 1 This is the ESEM image of the catalyst of the present invention. It can be seen from the figure that the overall structure of grapefruit peel biochar (PPBC) is relatively compact, and its surface shows uneven characteristics (Figure a). After nitrogen doping, the surface morphology of the material changes dramatically (Figure b). The doping of N atoms into the carbon network forms an obvious loose concave structure and wrinkled flaky layers on the surface of N@PPBC, indicating that N doping can significantly change the surface morphology of the material. After further iron and nitrogen co-doping, the surface of the Fe-N@PPBC material still maintains flaky layers and has a certain degree of fragmentation (Figure c). After further observation, it can be found that many particles are evenly embedded in the material, which are iron or iron oxides (Figures d to f).

[0064] 5. Pore structure of catalyst

[0065] The Brunauer-Emmett-Teller (BET) method was used to analyze the specific surface area and pore size of the catalyst. The specific surface area, pore size distribution and pore volume of the three prepared catalysts were evaluated by N2 adsorption-desorption isotherms. The results are shown in Table 1. Figure 2 shown.

[0066] Table 1 Parameters of specific surface area, pore size distribution and pore volume of catalysts

[0067]

[0068]

[0069] Table 1 shows the specific surface area, pore size distribution and pore volume parameters of the catalyst. It can be seen from the table that the specific surface area and pore volume of the material are greatly improved after doping with nitrogen and iron-nitrogen co-doping. The specific surface area and pore volume of PPBC are 68.027m 2 / g and 0.0748cm 2 / g, the specific surface area and pore volume of N@PPBC are 224.281m 2 / g and 0.2083cm 2 / g, the specific surface area and pore volume of Fe-N@PPBC are 334.468m 2 / g and 0.2232cm 2 / g. From the above ESEM analysis, it can be seen that after nitrogen doping, nitrogen atoms enter the carbon network, causing the material structure to change, presenting a loose flaky structure, and the specific surface area increases rapidly. Further iron-nitrogen co-doping continues to expand the specific surface area, which is because iron doping reduces the shrinkage of the carbon matrix during carbonization, and low-molecular-weight gases are converted from adjacent carbon materials. In addition, Fe-N@PPBC also has a smaller average pore size, which is conducive to the diffusion of organic pollutants into the carbon structure, thereby being further adsorbed or degraded.

[0070] Figure 2 : is the pore size distribution diagram of the catalyst of the present invention. It can be seen from the figure that the pore sizes of the catalyst of the present invention are mostly concentrated between 2 and 10 nm, and it is a typical mesoporous structure material.

[0071] 6. Crystal structure of catalyst

[0072] The present invention uses a RINT 2000 X-ray diffractometer (XRD, Japan, Rigaku) ​​to collect the XRD spectrum of the sample, using monochromatic Cu Kα radiation (40kV, 40mA) and a scanning rate of 1min-1. The results are as follows Figure 3 shown.

[0073] Figure 3 The XRD spectrum of the catalyst of the present invention shows that N@PPBC and Fe-N@PPBC have broad diffraction peaks at about 23°, corresponding to the non-crystalline diffraction peak of C(002). The intensity of the diffraction peak is obvious, indicating that it has a large degree of graphitization. In addition, the Fe-N@PPBC catalyst also shows obvious characteristic diffraction peaks of iron species, corresponding to the standard Fe 0 (PDF#06-0696), Fe3C (PDF#35-0772) and Fe3O4 (PDF#28-0491). 0 , Fe3C and Fe3O4 were successfully doped into the catalyst.

[0074] 7. Elemental composition and chemical state of catalyst

[0075] The present invention uses an X-ray photoelectron spectrometer (XPS, USA, PHIQuantera II) to detect the composition, content, valence and other information of the elements (such as C, N, O, Fe) of the catalyst.

[0076] It can be found that the surface elements of Fe-N@PPBC are composed of C (86.49%), O (6.57%), N (6.54%), and Fe (0.36%). The nitrogen structures include: pyridinic nitrogen (28.5%), pyrrolic nitrogen (29.29%), graphitic nitrogen (34.80%), and nitrogen oxide (7.41%). The high content of graphitic nitrogen and pyrrolic nitrogen acts as anchor points for iron atoms, promoting electron transfer. Graphitic nitrogen is the most active site in the reaction, and its presence provides more active sites for the Fe-N@PPBC catalyst, which is beneficial to the reaction. Oxygen structures include: Fe-O, C=O and C-OH. Fe structures include: Fe 0 , Fe 2+ , Fe 3+ , and Fe 0 , Fe 2+ , Fe 3+ The presence of provides the catalyst with the ability to activate free radicals.

[0077] Example 2

[0078] Degradation of BPA by Activating PMS with Different Catalyst Systems

[0079] The test method for catalytic degradation is: add 100mL of BPA solution to a 250mL beaker, add the catalyst and disperse it ultrasonically for 10min, then continue stirring for 30min to allow the system to reach adsorption-desorption equilibrium, then inject the PMS stock solution into the solution and stir. Take 0.5mL of the reaction solution, inject 1mL of methanol to quench the active oxygen species, and then filter the mixed solution with 0.22μm polytetrafluoroethylene into a liquid phase vial for subsequent analysis. Methanol can desorb BPA on the catalyst surface (desorption rate > 90%). Therefore, adsorption removal of BPA can be excluded.

[0080] 1. Comparison of different catalyst systems in activating PMS to degrade BPA

[0081] 1) The efficiency of BPA degradation in PMS, PPBC / PMS, N@PPBC / PMS and Fe-N@PPBC / PMS systems was measured. All systems were pre-adsorbed for 40 min to ensure adsorption saturation, which would not affect the performance comparison of subsequent catalytic experiments. Figure 4 shown.

[0082] Figure 4The removal rate of BPA under different catalytic systems is shown in the figure. It can be seen from the figure that PMS has basically no catalytic degradation ability without activation, but after adding the prepared biochar catalyst, the degradation rate of BPA has increased to varying degrees. Within 10 minutes, the degradation rates of BPA in PPBC / PMS, N@PPBC / PMS, and Fe-N@PPBC / PMS systems increased to 23.94%, 78.91%, and 95.14%, respectively. After N doping, the catalytic performance was greatly improved, which is also consistent with the previous characterization analysis. Compared with PPBC, N@PPBC has a large number of pores exposed on the surface, providing good adsorption capacity and abundant active sites. The large number of N=C active sites provided by N doping may play a key role in it. On the basis of N doping, Fe doping is further supplemented, and the catalytic performance is further improved. In order to accurately verify the catalytic ability of Fe-N@PPBC, a control group without PMS was set up for comparison to exclude the influence of adsorption. Combined with the previous characterization analysis, Fe-N@PPBC is rich in graphitic nitrogen, pyridinic nitrogen and oxygen-containing groups, which helps to improve the catalytic ability. At the same time, the porous structure of Fe-N@PPBC is embedded with iron-based crystals (Fe0, Fe3C and Fe3O4), providing more active sites.

[0083] 2) The performance of Fe-N@PPBC and other biochar catalysts in activating PMS to degrade BPA was compared, and the results are shown in Table 2.

[0084] Table 2 Comparison of BPA degradation efficiency of Fe-N@PPBC and other biochar catalysts

[0085]

[0086] Table 2 is a comparison of the BPA degradation efficiency of Fe-N@PPBC and other biochar catalysts. It can be seen from the table that when the dosage of biochar catalyst and PS activator is small and the BPA concentration is high, the BPA degradation rate can reach 100% within 20 minutes. This shows that the Fe-N@PPBC catalyst has excellent catalytic activity.

[0087] 2. Fe-N@PPBC activation of PMS to degrade BPA under different factors

[0088] 1) Catalyst dosage

[0089] Changing the dosage of Fe-N@PPBC, activating PMS to degrade BPA (the concentration of BPA solution is 10 mg / L, the dosage of PMS is 0.1 g / L), the results are as follows Figure 5 shown.

[0090] Figure 5The graph of the dosage of the Fe-N@PPBC catalyst of the present invention on the BPA removal rate (a) and the reaction rate constant (b) shows that as the dosage of the Fe-N@PPBC catalyst increases, the degradation rate constant of BPA gradually increases (Figure b). This is because the increase in the catalyst provides more adsorption sites for PMS and pollutants and PMS activation sites for the catalytic degradation process, which helps to shorten the reaction path between the catalytic material, PMS and pollutants and enhance the catalytic ability of the system. Fe-N@PPBC catalysts with different dosages have a good degradation effect on BPA, and the degradation rate exceeds 95% at 30 minutes. When the catalyst dosage is equal to 0.1g / L, the removal efficiency of BPA in the catalytic system within 10 minutes is as high as 95.7%. When the Fe-N@PPBC catalyst dosage is further increased to 0.2g / L, the BPA degradation performance is improved to a certain extent (kobs from 0.157min -1 Increased to 0.196min -1 ), but at 20 minutes, both 0.1g / L and 0.2g / L catalyst dosages can degrade 100% of pollutants. Therefore, from the economic perspective of actual engineering applications, the default catalyst dosage for subsequent tests is 0.1g / L.

[0091] 2) PMS dosage

[0092] Changing the dosage of PMS to degrade BPA (the concentration of BPA solution is 10 mg / L, the dosage of Fe-N@PPBC is 0.1 g / L), the results are as follows Figure 6 shown.

[0093] Figure 6 The graph of the PMS dosage of Fe-N@PPBC of the present invention on the BPA removal rate (a) and the reaction rate constant (b) shows that with the increase of PMS dosage, the BPA removal rate increases accordingly. When the PMS dosage is 0.05g / L, the BPA degradation rate within 5min is 81% (kobs is only 0.0567min -1 ), when the PMS dosage increased to 0.1 g / L, the BPA degradation rate was 93% (kobs increased to 0.152 min -1 ), its degradation efficiency is significantly improved. This shows that at a higher PMS dosage, Fe-N@PPBC catalyst can more quickly and efficiently activate PMS to produce more reactive oxygen species (ROS). It was mentioned in previous reports that adding excessive PMS to the reaction system may inhibit the degradation process, because SO4 ·- Can be self-cleaned, and S2O8 2- Reaction to generate S2O8 ·-This phenomenon is explained as sulfate radical quenching. Compared with the addition of 0.1g / L PMS, when an excess of PMS (0.2g / L) was added to the reaction system, no inhibitory effect was observed on the degradation process; on the contrary, the degradation efficiency of BPA was significantly improved (k increased from 0.19min-1 to 0.726min-1). It can be concluded that sulfate radicals are not the main oxidant in the catalytic reaction.

[0094] 3) Pollutant concentration

[0095] The initial pollutant concentration was 5-40 mg / L to test the degradation efficiency of Fe-N@PPBC on BPA (the dosage of Fe-N@PPBC was 0.1 g / L and the dosage of PMS was 0.1 g / L). The results are as follows Figure 7 shown.

[0096] Figure 7 The figure shows the relationship between pollutant concentration and BPA removal rate (a) and reaction rate constant (b). It can be seen from the figure that the removal performance and degradation rate of Fe-N@PPBC for BPA decrease with the increase of BPA concentration. When the BPA concentration is 5, 10, 20, and 40 mg / L, the degradation rates at 10 min are 95.37%, 94.72%, 91.15%, and 72.19%, respectively. In this catalytic system, for high concentration BPA (40 mg / L), the system can still achieve a degradation rate of 81.15% within 30 min, which shows that the degradation effect of the system is good.

[0097] 4) Solution pH

[0098] Solution pH is an important factor affecting the persulfate activation system, so the degradation performance of BPA at different initial solution pH was tested (Fe-N@PPBC dosage was 0.1 g / L, PMS dosage was 0.1 g / L, and BPA solution concentration was 10 mg / L). Figure 8 shown.

[0099] Figure 8 The graph of the system pH on BPA removal rate (a) and reaction rate constant (b) shows that the Fe-N@PPBC / PMS system has a good adaptability to the initial pH value, maintaining a high degradation rate at the initial pH of 3 to 9, and the BPA degradation efficiency reaches more than 95% within 10 minutes. However, when the initial pH of the solution is 10.84, the BPA degradation efficiency is inhibited to a certain extent in the system.

[0100] 5) Coexisting anions

[0101] The various anions present in the actual water environment will have different interference effects on the persulfate catalytic system, thereby affecting the catalytic activity of the system. The anti-anion interference ability of the Fe-N@PPBC activated PMS system was tested, and the effect of the coexistence of different anions on BPA and degradability was tested (the dosage of Fe-N@PPBC was 0.1g / L, the dosage of PMS was 0.1g / L, and the concentration of BPA solution was 10mg / L). The results are as follows Fig. 9 shown.

[0102] Fig. 9 The effect of coexisting ions on BPA removal rate (a) and reaction rate constant (b) are shown in the figure. It can be seen that NO3 - and SO4 2- The effect on BPA degradation is negligible, indicating that the catalyst has a strong anti-interference ability to these two anions during BPA degradation. - When the degradation rate of BPA increases to a certain extent (k value increases to 0.198min -1 ), which is due to the Cl - Can be converted into active chlorine free radicals with higher redox potential.

[0103] Example 3

[0104] Reusability and stability

[0105] After the catalytic experiment, the catalyst was separated and recovered by vacuum filtration, and then placed in a 50% methanol solution for oscillation desorption. After 24 hours, it was washed with pure water and dried overnight in a thermostat at 60°C. The obtained catalyst was reused in the cyclic degradation experiment. Fig.10 shown.

[0106] Fig.10 Figure 1 shows the recycling performance of Fe-N@PPBC (a) and the iron ion leaching concentration in a single cycle (b). As shown in Figure a, the activation ability of the catalyst will gradually decrease with the increase in the number of cycles. After the second and third repeated experiments, the degradation rate of BPA gradually decreased to 84.9% and 72.2%, respectively. After three cycles of experiments, due to the large number of active sites on the catalyst surface, the degradation rate can still be maintained at over 70%. In order to reactivate the catalyst, the catalyst used for the third time was re-calcined to remove the interference of surface organic pollutant adsorption. After heat treatment, the catalytic performance of Fe-N@PPBC was restored to a certain extent, and the re-treated Fe-N@PPBC / PMS catalytic system can degrade 83.2% of BPA within 30 minutes.

[0107] Example 4

[0108] Test of BPA treatment capacity in actual water bodies

[0109] Using tap water and Xuanwu Lake water as the background, the degradation of BPA in the Fe-N@PPBC / PMS system was tested in the actual water sample background. The results are as follows: Fig.11 And as shown in Table 3.

[0110] Table 3 Water quality indicators of Xuanwu Lake

[0111]

[0112] Table 3 shows the water quality indicators of Xuanwu Lake. Fig.11 The figure shows the removal rate of BPA in the water of Xuanwu Lake / tap water by the Fe-N@PPBC / PMS system. It can be seen from the figure that the removal rates of BPA in tap water and Xuanwu Lake water are 96.8% and 79.6% respectively. The degradation effect in Xuanwu Lake water is reduced because there are some natural organic matter and salts in it, which inhibit the removal of BPA. In comparison, the overall removal rate of BPA is close to 80%, indicating that the Fe-N@PPBC catalyst of the present invention has good application prospects in removing organic pollutants in actual water bodies.

[0113] Example 5

[0114] Broad-spectrum test of Fe-N@PPBC / PMS system’s ability to degrade organic pollutants

[0115] The degradation effect of Fe-N@PPBC / PMS system on different types of pollutants was tested, including sulfadimethoxine (SMT), sulfadiazine (SDZ), rhodamine B (RhB), tetracycline (TC), and ciprofloxacin (CIP). Fig.12 shown.

[0116] Fig.12 The figure shows the removal rate of different pollutants by Fe-N@PPBC / PMS system. The reaction conditions are: catalyst 0.1g / L, PMS 0.1g / L, SMT, SDZ, TC and CIP 10mg / L, RhB 30mg / L. It can be seen from the figure that under the same dosage of Fe-N@PPBC (0.1g / L) and PMS (0.1g / L), the degradation rates of SMT, SDZ, RhB, TC and CIP are 99.8%, 98.9%, 86.6%, 71.8% and 61.2% respectively within 30min. Fe-N@PPBC has the best degradation effect on sulfonamide compounds (SMT, SDZ), which can be degraded by more than 95% within 1min.

Claims

1. A method for rapid degradation of BPA based on activation of PMS by iron-nitrogen co-doped grapefruit peel biochar, characterized in that: The iron-nitrogen co-doped grapefruit peel biochar is mixed with a BPA solution, ultrasonically stirred, and then a PMS stock solution is added and stirred to degrade BPA; wherein the amount of the iron-nitrogen co-doped grapefruit peel biochar is 0.05 g / L to 0.2 g / L.

2. The method for rapid degradation of BPA based on activation of PMS by iron-nitrogen co-doped grapefruit peel biochar according to claim 1, characterized in that: The dosage of the iron-nitrogen co-doped grapefruit peel biochar is 0.1 g / L.

3. The method for rapid degradation of BPA based on iron-nitrogen co-doped grapefruit peel biochar activated PMS according to claim 1, characterized in that: The usage of the PMS is 0.05 g / L to 0.2 g / L.

4. The method for rapid degradation of BPA based on iron-nitrogen co-doped grapefruit peel biochar activated PMS according to claim 3, characterized in that: The dosage of the PMS is 0.1 g / L.

5. The method for rapid degradation of BPA based on activation of PMS by iron-nitrogen co-doped grapefruit peel biochar according to claim 1, characterized in that: The concentration of the BPA solution is 5-40 mg / L.

6. The method for rapid degradation of BPA based on activation of PMS by iron-nitrogen co-doped grapefruit peel biochar according to claim 5, characterized in that: The concentration of the BPA solution is 10 mg / L.

7. The method for rapid degradation of BPA based on iron-nitrogen co-doped grapefruit peel biochar activated PMS according to claim 1, characterized in that: The initial solution pH of the iron-nitrogen co-doped grapefruit peel biochar / PMS system is 3-9.

8. The method for rapid degradation of BPA based on activation of PMS by iron-nitrogen co-doped grapefruit peel biochar according to claim 7, characterized in that: The initial solution pH of the iron-nitrogen co-doped grapefruit peel biochar / PMS system is 3-8.

9. A method for preparing iron-nitrogen co-doped grapefruit peel biochar, characterized in that: The specific steps are as follows: 1) crushing the grapefruit peel and sieving it through a 100-mesh sieve to obtain grapefruit peel powder; 2) adding pomelo peel powder, urea, FeSO4·7H2O and ascorbic acid into deionized water, stirring magnetically to dissolve, then placing into an autoclave and hydrothermally heating at 190°C for 6 hours, centrifuging after the hydrothermal reaction, collecting the precipitate, and freeze-drying at -60°C for 36 hours to obtain hydrothermal pomelo peel charcoal; wherein the mass ratio of pomelo peel powder, urea, FeSO4·7H2O and ascorbic acid is 1:1:0.6-0.8:0.3-0.5; 3) The hydrothermal grapefruit peel charcoal prepared in step 2) was placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min, and calcined for 2 hours under N2 protection. After the calcination, it was first washed with 5 mol / L hydrochloric acid for 12 hours, and then washed with deionized water for 3 times to prepare an iron-nitrogen co-doped grapefruit peel biochar catalyst.

10. Use of the iron-nitrogen co-doped grapefruit peel biochar prepared by the method of claim 9 in the degradation of BPA.

Citation Information

Cited By

  • Synthesis method and application of iron-aluminum co-doped catalyst

    CN120205207A